Topical Probiotic Hydrogels for Burn Wound Healing - Tavinda Arshad; Varsha Mundrathi; Victoria E. Perez; Jeilyn M. Nunez; Hyunah Cho (Gels, 2024)
Hydrogels have increasingly been used to enhance the effective healing of various wounds, including burn wounds. Similarly, the application of probiotics has recently been explored in wound healing and skin repairs. While probiotics have been consumed to provide therapeutic effects that aid with improving gut health, topical applications have been found to accelerate wound healing both in vitro and in vivo. For wounds that have complex healing mechanisms, such as burn wounds which depend on factors such as the depth of the burn, size of the afflicted area, and cause of the injury, probiotics with or without conventional therapeutic agents topically delivered via hydrogel technology are proven to be effective in the recovery of the damaged skin. This article aims to investigate the microorganisms present in the human skin microbiome and observe the effects of probiotics delivered by hydrogels on burn wound healing.